JENIS DAN POPULASI SERANGGA HAMA YANG BERASOSIASI PADA TANAMAN KENTANG (Solanum tuberosum L) DI KECAMATAN MODOINDING - Audy R. Bororing; Juliet M.E. Mamahit; Daisy S. Kandowangko; Noni N. Wanta (COCOS, 2015)
ABSTRACTThe research aims to find out about the type of insect pests population in potato plants Solamun tuberosum L. in Modoinding, South Minahasa. The research was conducted on the potato plants in Modoinding, South Minahasa. The research was carried out by using the survey method on potato in Modoinding's villages, South Minahasa, such as Palelon Village, Makaaroyen Village, and Lineleyan Village. The sampling was carried out with a diagonal incision method that established of five sub-plot that is on the corner and the middle of the sampling sites. The sampling was done by using insect nets that swung above the potato crop for ten times the double swing. The netted insects are immediately put into the "killing bottle" then collected in 70% alcohol to be identified. Identifying the type of insect pests is done by using the facilities of the Entomology and Pest Plant Laboratory, Faculty of Agriculture, UNSRAT. The results of the research of the associated pests on potato was found about eight kinds of insect pests, such as Empoasca sp. 109.03, Drosophila sp. 37.03, Nesidiocoris sp. 34.11, Lirionyza sp. 10.72, Lygus sp. 4.47, Phthorimaea sp. 2.97, Antractomorpha sp. 1.61, and Epilachna sp. 0.69. The average of the highest populations of insect pests are found in Makaaroyen Village with 37.99, whereas in Palelon Village with 22.79, and the lowest is in rural Lineleyan Village with 14,49.Keywords: Population, Pest, Potato